Delivering on the Promise of Biological Control in Asia's Food Systems: A Humboldtian Perspective - Wyckhuys, Kris A.; González-Chang, Mauricio; Adriani, Evie; Albaytar, Annabelle; Albertini, Alice; Ávila, Gonzalo; Beltran, Marie Joy; Boreros, Ariel; Fanani, Muhammad Z.; Nguyễn, Duc T.; Nguyễn, Giang; Nurkomar, Ihsan; et al. (Frontiers in Sustainable Food Systems, 2020)
During the late twentieth century, the “Green Revolution” attained wide-ranging poverty alleviation, food security and improved nutrition across rural Asia. As these achievements were often reached at large environmental costs, “greener” trajectories urgently need to be traced for Asia's agri-food systems. In this sense, agro-ecological and biodiversity-based (ABB) farming systems can provide sufficient food, lift resource-use efficiencies and lower fossil-fuel dependencies while safeguarding the environment. Here, we systematically assess past progress and prospects for biodiversity-based pest management -or biological control (BC)- in five Asian countries. We characterize the extent to which BC science has matured, translated into practice and attained “real-world” outcomes within the prevailing farming systems of each country. To achieve this, we revert to the world-view of the eighteenth century naturalist Alexander von Humboldt. Doing so, we represent the extent to which BC science has progressed along a six-step “impact pathway” –from a description of on-farm biodiversity, over ecosystem service delivery to verifiable socio-economic outcomes. Our work pinpoints ways to strategize ABB science for an accelerated, evidence-based uptake by end-users within local agri-food systems. By entwining our Humboldtian “nature-culture” perspective with farmer-scientist co-innovation, bolstered awareness-raising and supportive policies, ABB farming transitions could be initiated that are prone to deliver concrete, desirable agro-ecological outcomes at local and regional scales.